Design and development of a two post rotary-percussion drilling rig - Borlagdan, Paterno C. (Philippine Engineering Journal)
A two post-Rotary Percussion drilling rig (AMDP Model 2 Drilling Rig) for shallow tubewell irrigation development was successfully developed at the Agricultural Mechanization Development Program, University of the Philippines at Los Baños. Consisting of a 5 horsepower horizontal shaft gasoline engine as the prime mover for rotary drilling, 4 horsepower direct coupled water pump for jetting, overhead platform mounted on two post system, a reduction gear box, hoist and cable system sub-assembly, sliding engine mount sub-assembly and basic strut supports; it is capable of drilling into various soil formations up to 100 feet and even deeper.